Comparison of neuroprotective effect of isoflurane and sevoflurane on cerebral ischemia - Sayan, Halil Erkan; Muslu Erdem, Vuslat; Korfalı, Şefika Gülsen (The European Research Journal, 2020)
Objectives: In this study, we aimed to evaluate the effects of isoflurane and sevoflurane on cerebral ischemia in patients undergoing intracranial tumour surgery by measuring protein S-100B in serum. Patients undergoing intracranial surgery are at risk for cerebral ischemia. The presence of S100-B in serum is an early and the most sensitive determinant of cerebral ischemia.Methods: Twenty patients, scheduled for elective, intracranial tumor surgery were enrolled in this prospective and randomized study. Anaesthesia induction was performed with thiopental, fentanyl and vecuronium. In the maintenance, isoflurane or sevoflurane was administered in a minimum alveolar concentration of 0.8-1.2%. Peripheral blood samples were taken at 9 different times to measure protein S-100B levels.Results: Demographic data, heart rate, systolic arterial pressure, mean arterial pressure and the deviations in the end-tidal carbon dioxide were similar in the study groups (p > 0.05), whereas diastolic arterial pressure was found to be significantly decreased in isoflurane group after the intubation, and there was an increase in the sevoflurane group (p < 0.05). Also there was no significant difference between the groups regarding protein S-100B levels. Conclusions: It was concluded that isoflurane and sevoflurane have similar neuroprotective effects against cerebral ischemia and sevoflurane may be a good alternative to isoflurane.